Banking and the Evolving Objectives of Bank Regulation - Diamond, Douglas W.; Kashyap, Anil K.; Rajan, Raghuram G. (Journal of Political Economy, 2017)
Views on the role played by banks in the economy have evolved greatly over the last 125 years, as have arguments on the need, as well as the best way, to regulate them. Some of the key insights in the debate have been published in the Journal of Political Economy. In what follows, we will outline the main contributions to the debate in recent years, with an emphasis on work done at the University of Chicago or published in the JPE. We want to emphasize work that has relevance today, but despite this caveat, we will probably end up doing injustice to work published long ago. We begin with a framework for organizing the theories of intermediation. We then draw out the implications for what the theories say about regulation and note that in many respects the motivation for regulation has been only loosely tied to the theory of intermediation. We close with some open questions for regulators and economists interested in banking. We do not survey the research that has followed up on work published in the JPE, nor will we attempt to provide a detailed overview of the entire academic literature on banking. For that, we refer the reader to the excellent work by Gorton and Winton (2003) and Freixas and Rochet (2008).